The importance of developmental relations in the workplace - Šarotar Žižek, Simona (Anali PAZU HD, 2022)
Interpersonal relations in the workplace present the relations between colleagues and relations with superiors and subordinates; the narrower concept of interpersonal relations present developmental relations in the workplace, which represent relationships between employees and are focused on developing and exploiting the potentials of individuals and creating a climate of cooperation. In order to maintain balanced relationships, employees need both opportunities for giving and receiving (emotional or instrumental) support. Interpersonal or emotional support can involve anything that helps the individual. The purpose of the paper is to determine whether there are different qualities of developmental relations and whether developmental relations affect individual performance of an individual. We have confirmed that there are different qualities of development relations and that high quality relationships cause interaction, growth and learning of individuals. We also confirmed the hypothesis that quality development relations have a significant impact on person’s individual performance.